Disclosure of the value at risk (VaR) before the crisis in the Spanish banking sector (2019)
Risk management has assumed great importance in financial institutions. Banks disclose their exposure to market risks in the form of value-at-risk (VaR). This paper evaluates the disclosure of this risk management measure in the Spanish banking sector prior to the Spanish crisis started in 2008. Based on a content analysis of the annual reports of banks in Spain, twelve items were analyzed as to the quality of the information relating to VaR. This study shows that the disclosure made prior to the crisis was poor in terms of quality and comparability. Also it was observed that the quality of the information provided about the VaR was associated positively to bank size. The Spanish banking sector case highlights the importance of upgrading financial supervision and risk management practices.